The Impact of Drug Dependence on Scrupulosity among Young Adult Drug Dependents - Maryam Naveed; Dr. Anila Sadaf (Indus Journal of Social Sciences, 2025)
The increasing prevalence of drug dependence among young adults has increased considerable public health issues, with emerging studies indicating a complicated relationship between drug use and psychological manifestations such as scrupulosity. This study examined the impact of drug dependence on scrupulosity among young adult drug dependents. The primary objective was to assess the impact of drug dependence on scrupulosity, as well as to explore the predictive role of drug dependence on scrupulosity. A cross-sectional survey design was employed, utilizing purposive sampling to collect data from 270 drug dependents aged 18 to 28 years from rehabilitation centers and clinics in Islamabad and Rawalpindi. Data were gathered using the Severity of Dependence Scale (Gossop et al., 1995), and Pennsylvania Inventory of Scrupulosity (Abramowitz et al., 2002). Statistical analyses, including correlational analysis, regression and ANOVA were conducted. Findings suggested that a positive significant correlation exist between the drug dependence and scrupulosity (r = 0.13, p < 0.001), indicating that as drug dependence increased, scrupulosity tended to increase slightly. The severity of dependence on drugs strongly predicted a person's scrupulosity scores (β =0.43, p < 0.05). Given the limited research on this relationship in Pakistan, this study focuses on a crucial gap in the existing literature and emphasizes the need for further investigation of the relationship between drug dependence and scrupulosity in this specific population.